Kerangka Kurikulum Pendidikan Agama Kristen Berbasis Karakter di Perguruan Tinggi - Binsen Samuel Sidjabat (Jurnal Jaffray, 2019)
This article proposes a curriculum framework of character based Christian religious education in higher learning institutions. To make it happen, the concept of character education according to the Christian faith is explained, character education in universities is disclosed, and the Christian religious education curriculum framework is described. Then, the author proposes a Christian religious education curriculum framework based on character education.